La inconstitucionalidad del procedimiento directo en los delitos flagrantes en su articulo 640 numeral 4 del Código Orgánico Integral Penal - Feijoo Zumba, Carlos Rene (2016)
The research Below is framed in the field of legal research, specifically directed to conduct a study on the direct method provided for in the Code of Criminal Integral.This research project is justified should consider the implications of applying the direct method as an agile a criminal case. (CRIMES GROSS / UNDER 5 YEAR). Direct criminal procedure poses a facile solution to the effectiveness of criminal justice in quick decongestion of the causes, not as an introduction covered by the basic fundamental guarantees and reflected in due process, which would lead to significant and profound changes; It is for this reason that I consider it necessary to strengthen and deepen the eligibility of the same. As our Constitution accurately determined principles and rights concerning criminal process cause. The subject of direct criminal procedure, is an issue that has been much discussed in all countries of the world; subject to many legal systems have found acceptance; and, that in our country the way it is regulated not given the necessary respect for the fundamental rights of people who undergo this procedure. Our legislation, however, so far has not found a reform on the issue, so in view of the existing legal framework is necessary to reform this legal institution, in order to fulfill its role as is the completion of criminal proceedings short, where however be observed as standard maximum respect for the human rights of the parties